Study on the electrical-thermal properties of lithium-ion battery materials in the NCM622/graphite system - Li, Hao; Wu, Xv; Fang, Sheng; Liu, Mei; Bi, Shansong; Zhao, Ting; Zhang, Xiangjun (Frontiers in Chemistry, 2024)
The phenomenon of fire or even explosion caused by thermal runaway of lithium-ion power batteries poses a serious threat to the safety of electric vehicles. An in-depth study of the core-material thermal runaway reaction mechanism and reaction chain is a prerequisite for proposing a mechanism to prevent battery thermal runaway and enhance battery safety. In this study, based on a 24 Ah commercial Li(Ni0.6Co0.2Mn0.2)O2/graphite soft pack battery, the heat production characteristics of different state of charge (SOC) cathode and anode materials, the separator, the electrolyte, and their combinations of the battery were investigated using differential scanning calorimetry. The results show that the reaction between the negative electrode and the electrolyte is the main mode of heat accumulation in the early stage of thermal runaway, and when the heat accumulation causes the temperature to reach a certain critical value, the violent reaction between the positive electrode and the electrolyte is triggered. The extent and timing of the heat production behaviour of the battery host material is closely related to the SOC, and with limited electrolyte content, there is a competitive relationship between the positive and negative electrodes and the electrolyte reaction, leading to different SOC batteries exhibiting different heat production characteristics. In addition, the above findings are correlated with the battery failure mechanisms through heating experiments of the battery monomer. The study of the electro-thermal properties of the main materials in this paper provides a strategy for achieving early warning and suppression of thermal runaway in batteries.